2021
DOI: 10.3390/children8100870
|View full text |Cite
|
Sign up to set email alerts
|

Development of Social Skills in Kindergarten: A Latent Class Growth Modeling Approach

Abstract: Social skills acquired during early childhood are often the foundation for success later in life. Using a nationwide survey dataset in Japan, this study aims to explore the multiple growth trajectories of social skills among children in kindergarten by using a latent class growth modeling approach. It also examines whether, and to what extent, the home-rearing environment at early age predict trajectories of social skills development. Children in this study were assessed on social skills at three waves, four h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The results also revealed that children whose mothers had higher PCEs were less likely to have psychosocial difficulties. Parents with higher PCEs may be more likely to generate feelings of kindness, compassion, and security in their children (Narayan et al, 2019 ), which may enhance parent–child relationships and decrease the risk of behavioural problems (Zhu et al, 2021 ). More PCEs in childhood may lead to better long-term mental health outcomes and fewer chronic health problems as children age (Shaw et al, 2003 ), which may reduce the risk of psychological problems in children (Boursnell, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results also revealed that children whose mothers had higher PCEs were less likely to have psychosocial difficulties. Parents with higher PCEs may be more likely to generate feelings of kindness, compassion, and security in their children (Narayan et al, 2019 ), which may enhance parent–child relationships and decrease the risk of behavioural problems (Zhu et al, 2021 ). More PCEs in childhood may lead to better long-term mental health outcomes and fewer chronic health problems as children age (Shaw et al, 2003 ), which may reduce the risk of psychological problems in children (Boursnell, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…This trend of relationship is indicative of maladjustment among ADHD adolescents. The importance of supervision and discipline are very crucial elements during development in acquiring good social and academic skills in general (i.e., accomplishing daily tasks and homework) (Zhu et al, 2021;Loe et al, 2007;Aduen et al, 2018). It is also evident that lack of discipline may further complicate the behavioral and social difficulties of children and adolescents with ADHD (Teixeira et al, 2015;Tung, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Family is the first health avenue for children. Studies have shown that parents’ positive engagement with children in social activities is correlated with children’s general emotional and behavioral development [ 21 , 22 ]. A positive parent–child relationship can be a protective factor against children’s internalizing or externalizing behavioral problems [ 23 , 24 ], and this relationship can be encouraged by family activities, such as playing games and sharing meals [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%